Initial impacts of COVID-19 on youth offending: An exploration of differences across communities - McCarthy, Molly (Journal of criminology, 2021)
A number of international studies have found that the initial stages of the COVID-19 pandemic were associated with reductions in crime, primarily due to changes in the routine activities of the population. However, to date there has been no targeted exploration of how COVID-19 may have influenced youth offending, which may be more heavily impacted by the changes heralded by COVID-19 containment measures. This study examines changes in youth offending in an Australia jurisdiction, Queensland, following the implementation of COVID-19 containment measures from the period April to June 2020. Additionally, differences in impacts across community types were explored. Findings from the panel regression indicated significant declines in youth property offending, offences against the person and public order offences in this period, but no significant changes in illicit drug offences. There were also significant differences across communities according to socio-economic status, per cent Indigenous population, and the extent of commercial or industrial land use. Findings are explored with reference to environmental crime theories and the potential impacts of social, economic and policing changes that occurred in this period.